2014
DOI: 10.1089/omi.2013.0164
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Animal Model of Ovarian Cancer: Cataloging Chicken Blood Proteins Using Combinatorial Peptide Ligand Libraries Coupled with Shotgun Proteomic Analysis for Translational Research

Abstract: Epithelial ovarian cancer is the most deadly gynecological cancer around the world, with high morbidity in industrialized countries. Early diagnosis is key in reducing its morbidity rate. Yet, robust biomarkers, diagnostics, and animal models are still limited for ovarian cancer. This calls for broader omics and systems science oriented diagnostics strategies. In this vein, the domestic chicken has been used as an ovarian cancer animal model, owing to its high rate of developing spontaneous epithelial ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…To examine the contribution of transparent fluid to the RJF SF proteome, we investigated overlap with existing proteomic data from domestic chicken blood plasma36. This revealed that 52.1% (137 out of 263) of identified blood plasma proteins were present in RJF SF (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the contribution of transparent fluid to the RJF SF proteome, we investigated overlap with existing proteomic data from domestic chicken blood plasma36. This revealed that 52.1% (137 out of 263) of identified blood plasma proteins were present in RJF SF (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The same analysis pipeline was used to reanalyze available raw MS/MS data from fractionated domestic chicken SF samples24. SF proteomes were compared to the chicken blood plasma proteome36, the exosome ExoCarta high quality protein marker dataset47, human blood plasma37, human sperm41, mouse epididymal sperm42 and human seminal plasma35 using orthology relationships in Ensembl Genes 84 (Galgal4). Composition of protein datasets were analyzed using the DAVID Bioinformatics Resource (6.7)8081, including statistical analyses of functional enrichment using the G. gallus genome as the background dataset for comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge of OC proteome into different conditions is essential for planning future treatment strategies. Although a considerable number of proteomic approaches in animal models with OC have recently been tested, ,, clinical applications remain lower than optimal. Thus we performed a comparative analysis between OC and OC treated with melatonin and reported an extensive catalogue of differentially expressed proteins that are affected by melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%